KONTRIBUSI KOMUNITAS NU DALAM ISU KELESTARIAN LINGKUNGAN HIDUP DI INDONESIA - M. Khoirul Huda (Jurnal Dialektika Politik, 2023)
This article discusses the contribution of the Nahdlatul Ulama (NU) elite in environmental sustainability issues in Indonesia during 1980-2015. Using the historical idea method, the author analyzes a number of documents and finds that evolutionarily, NU elites have been involved and made important contributions to environmental preservation. At least, there are three main contributions. First, the development of environmental fiqh thinking that is moral-ethical in nature about the necessity of preserving the environment. Two key NU figures who represent this spirit are KH. Ali Yafie (Rais Amm 1991-1992) and KH. Sahal Mahfudz (1999-2014). Second, raising Islamic boarding school scholars to create environmental sustainability discourses in the perspective of Islamic tradition. The Bahsul Masail study forums that characterize NU are filled with environmental issues. Both kiai caretakers and Islamic boarding school students are familiar with the issue of environmental sustainability. The climax is the emergence of calls for environmental jihad (jihad al-bi'iyyah). Third, the formation of environmental institutions in the organizational structure of NU. This contribution shows that religious groups can play an important role in spreading the idea of environmental sustainability. This finding is in line with the findings of Palmer and Finlay (2003), Barclay (2007) WWF (2010) regarding the effectiveness of religious communities in transmitting environmental preservation insights.